(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
In this paper, Endpoint Detection and Response (EDR) systems are analyzed to enhance the detecting and responding of a threat using secure and scalable microservices. The study employed quantitative technique on the basis of experimentation, testing, and data examination. Docker and Kubernetes were used to construct the system with microservices that were responsible in data ingestion, analytics, and alerts. Various capacities of microservices and security configurations which included basic TLS, zero-trust, and runtime trust were tested. Throughput and latency, accuracy of detection, and resource utilization were measured in the study. It was revealed that throughput enhanced by over 150 percent in microservices over monolithic systems. The error rate of detection reached 97 percent when there were runtime trust models. Time spent and time taken to recover also enhanced. The conclusion described in the paper is that EDR systems built on microservices have a greater speed, security, and scalability. They are also able to achieve goals of governance, compliance in an improved way compared to traditional set-ups. The study provides research evidence regarding how cloud-native and secure design patterns could be used to create efficient and reliable threat detection sites.